The other special relationship: race, rights, and riots in Britain and the United States - Kelley, Robin D. G.; Tuck, Stephen G. N. (Contemporary Black history, 2015)
Introduction / Robin D. G. Kelley and Stephen Tuck -- 1. "U.S. Negroes, Your Fight is Our Fight" : Black Britons and the 1963 March on Washington / Kennetta Hammond Perry -- 2. "Black Was the Colour of our Fight" : The Transnational Roots of British Black Power / Rosie Wild -- Individual Life: A Black Englishman in the Heart of the Confederacy : The Transnational Life of Paul Stephenson / Nick Juravich -- 3. Caribbean Left : Diasporic Circulations / Carole Boyce Davies -- 4. Scholar-Activist St. Clair Drake and the Transatlantic World of Black Radicalism / Kevin Gaines -- Individual Life: "We all became black" : Tony Soares, African-American internationalists, and anti-imperialism / Anne-Marie Angelo -- 5. A Heavy Load : The American Civil Rights Movement and the Northern Ireland Civil Rights Movement / Marc Mulholland -- 6. Containing Racism? : The London Experience, 1957-1968 / John Davis -- Individual Life: From Manchester to Monroe : The unexpected journey of Constance Lever / Stephen Tuck and Imaobong Umoren -- 7. "Nobody in This World Is Better Than Us" : Calypso in the Age of Decolonization and Civil Rights / Joshua B. Guild -- 8. Stax, Subcultures, and Civil Rights : Young Britain and the Politics of Soul Music in the 1960s / Joe Street -- Individual Life: From Guy Warren to Kofi Ghanaba : A Life of Trans-Atlantic (Dis)Connections / Robin Kelley -- 9. Violence at Desmond's Hip City : Gender and Soul Power in London / Tanisha C. Ford -- 10. Brotherhood, Betrayal, and Rivers of Blood : Southern Segregationists and British Race Relations / Clive Webb